128 Late-onset pompe disease (LOPD) presenting with fulminant hypercapnic respiratory failure. (29th July 2019) - Edwards, Leon S; Tchan, Michel; Crossley, Kate M; Yee, Brendon; Spies, Judith M
Abstract : Introduction: We report a case of LOPD with acute-on-chronic respiratory failure. Case: A 57 year-old retired farmer presented with obtundation requiring intubation. He reported a 4 month history of hypophonia, intermittent diplopia, lethargy and orthopnea. Initial arterial blood gas measurement displayed acute-on-chronic hypercapnic respiratory failure (pH 7.19, pO2 98 mmHg, pCO2 112 mmHg, HCO3 43 mmol/L). Muscle biopsy was suggestive of LOPD with myofibres demonstrating acid phosphatase and periodic acid-schiff positive vacuoles. Diagnosis was confirmed with low α-glucosidase activity on dried blood spot (0.4umol/h/L) and elevated urinary tetrasaccharide level (5 mmol/mol creatinine). Mutation analysis of the GAA gene demonstrated two known pathogenic mutations (c.-32–13T>G and c.1075+1G>T). With improved ventilation, he was able to be extubated. The only respiratory support on discharge was overnight bilevel positive airway pressure ventilation. Conclusion: LOPD is a rare autosomal recessive metabolic disorder caused by a deficiency in acid α-glucosidase. This leads to intra-lysomal accumulation of glycogen in tissues. Particularly in the late form, there is significant phenotypic variability. 1 Diagnosis remains challenging. Cases have been reported with a range of initial symptoms including stroke, 2 syncope 3 and chronic respiratory failure. 4 Acute on chronic respiratory failure at presentation is rare. Enzyme replacement therapy has been shown to improve both morbidity and mortality in LOPD. 5 Earlier treatment is associated with better outcomes. 6 Prompt recognition of cases is paramount. Unexplained acute-on-chronic respiratory failure should raise the possibility of this condition. In such cases, management of ventilation is vital. References: Chan J, et al. The emerging phenotype of late-onset Pompe disease: A systematic literature review. Mol Genet Metab 2017;120(3):163–172. Hossain MA, et al. A Case of Adult-onset Pompe Disease with Cerebral Stroke and Left Ventricular Hypertrophy. J Stroke Cerebrovasc Dis 2018;27(11):3046–3052. Walczak-Galezewska M, et al, Late-onset Pompe disease in a 54 year-old sportsman with an episode of syncope: a case report. Eur Rev Med Pharmacol Sci 2017;21(16):3665–3667. O'Callaghan C, et al, Adult-onset Pompe disease presenting with insidious hypercapnic respiratory failure. Respirol Case Rep 2016;4(5):e00178. Schoser B, S A, Kanters S, Hamed A, Jansen J, Chan K, Karamouzian M, Toscano A. Survival and long-term outcomes in late-onset Pompe disease following alglucosidase alfa treatment: a systematic review and meta-analysis. J Neurol 2017;264(4):621–630. Chien YH, HW, Lee NC. Pompe disease: early diagnosis and early treatment make a difference. Pediatr Neonatol 2013;54(4):219–227.